Jesus i oversettelse Kristologiske tekster i Bibelselskapets oversettelser 1959-2011 - Beckmann, Morten (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2019)
"Who is the biblical Jesus? The answer depends on which translation you read. Most people read their Bible translation as "the Bible". Publishers of the Bible have great power to define the Bible and decide how the biblical Jesus is presented. Jesus i oversettelse is a detailed analysis of the translation processes behind the making of eighteen Christological verses in the translations of the Norwegian Bible Society 1959-2011. Readers are invited to a process that few have access to: How the translations are made, and what considerations and which interests are reflected in the translation choices. To what extent do the translators ensure a distinct understanding of Jesus in the translated text? Do the translations change the meaning and message of the source text, or do the translations preserve the interpretative possibilities? What view of Jesus is reflected in translations of the Norwegian Bible Society? "